Effect of Planting Dates and Plant Spacing on Growth, Yield and Yield Components of Sunflower (Helianthus annuus L.) in Iraqi Kurdistan Region - Mahmood, Hekmat N. (Sulaimani Journal for Pure and Applied Sciences, 2013)
A field study was conducted in spring of 2011, at Kanipanka and Bakrajo, in the province of Sulaimani to evaluate the impact of planting dates and spacing on growth and yield of oilseed sunflower (Helianthus annuus L.), variety "Flame". The experiment comprised of three planting dates (March15th, 30th and April15th), and three-plant spacing (15, 20, and 25 cm). Seed yields obtained from earlier planting date and narrow plant spacing were significantly higher. The results also showed that the early planting date March15th has a significant positive effect on plant height, stem diameter, head size, and seed weight than the late planting date April15th as an average of both locations. The interaction between planting dates and plant spacing as an average of both locations, showed that March15th planting date and 25 cm plant spacing had significantly higher 1000 seed weight and seed weight per plant, while the highest seed yield gained by the interaction of March 15th and plant spacing 15cm. Percentage seed oil content collected as an average of both locations was significantly higher from plants with late planting date April 15th at 20 cm plant spacing. All the studied characters except seed oil percentage shows higher significant values at Kanipanka location due to the favorable agro- climatic condition compared to Bakrajo location.
Keywords: Sunflower; Planting Date; Plant Spacing; Yield and Yield Components